Detection of Y-STR Touch DNA for Personal Identification on a Wooden Knife Handle Used as a Stabbing Weapon - M, Boonpim; C, Kanchai; T, Bhoophat (Biomedical Sciences and Clinical Medicine, 2020)
Objectives The purpose of this study was to examine the effectiveness of Y-STR profiling of touch DNA from a woodenhandle knife used as a stabbing weapon. Methods A group of 60 male volunteers were asked to stab a foam box with a wooden-handle knife held firmly in their hand. DNA from the surface of the knife handles was extracted using a Qiagen® QIAamp DNA Investigator kit and amplified using a modified Investigator® Argus Y-12 QS protocol. Results The touch DNA profiling found that 6 of 60 of full profile samples (10%) gave a full profile and 21 samples (35%) showed useful partial profiles. No significant difference was observed between right- and left-hand dominant volunteers (p = 0.5615 95% CI = -24.6237 to 44.1160, Chi-squared test of proportion). Conclusion Y-STR profiling of touch DNA is suitable for use in conjunction with other personal identification methods.